2012
DOI: 10.1111/j.1748-3743.2012.00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Last three days of life in the hospital: a comparison of symptoms, signs and treatments in the young old and the oldest old patients using the Resident Assessment Instrument for Palliative Care

Abstract: With the exception of more falls and peripheral oedema in the oldest old patients, this study showed no differences in symptoms and treatment between the young old and the oldest old patients. Delirium was poorly documented compared to other studies. Implications for practice.  The oldest old patients have a higher risk of falls in the final phase of life, and fall prevention should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
(86 reference statements)
0
14
0
Order By: Relevance
“…Thorough clinical assessment on admission to and throughout hospice care and ongoing education of the patient and caregiver are essential to reduce the number of falls in this patient population. Fall assessment tools, which are commonly used to predict which patients are likely to fall or not, are designed for use in specific healthcare settings1–18 for a specific disease,7 13 19–22 for patients of a similar age3–6 10 14 16 20 23–25 or for general use 26–28. Previous reports compare the predictive values of one tool with another8 9 15 17 20 26 or evaluate the predictive value of a single tool,6 7 14 29 30 then fault the tool's predictive ability when it appears that the tool grossly overestimated or underestimated the likelihood of fall.…”
Section: Introductionmentioning
confidence: 99%
“…Thorough clinical assessment on admission to and throughout hospice care and ongoing education of the patient and caregiver are essential to reduce the number of falls in this patient population. Fall assessment tools, which are commonly used to predict which patients are likely to fall or not, are designed for use in specific healthcare settings1–18 for a specific disease,7 13 19–22 for patients of a similar age3–6 10 14 16 20 23–25 or for general use 26–28. Previous reports compare the predictive values of one tool with another8 9 15 17 20 26 or evaluate the predictive value of a single tool,6 7 14 29 30 then fault the tool's predictive ability when it appears that the tool grossly overestimated or underestimated the likelihood of fall.…”
Section: Introductionmentioning
confidence: 99%
“…All patients were recruited from the same hospital and routines, attitudes, knowledge and cultures may vary by hospital and country. Studies from other locations are warranted to replicate our findings and determine their generalisability (Steindal et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…() and Steindal et al . (), previous studies included few patients aged 65 years and older. Another study (Rashidi et al ., ) compared symptom burden, such as pain, and opioid administration in very old hospitalised patients (aged 80 years and older) and younger patients (aged 50–70 years) in the last three days of life.…”
Section: Introductionmentioning
confidence: 99%
“…The frequencies of symptoms in patients with advanced cancer have been reported . Knowledge of the prevalence of symptoms in patients with incurable cancer in the terminal stage is important for clinicians to provide appropriate care of cancer patients .…”
Section: Introductionmentioning
confidence: 99%
“…The frequencies of symptoms in patients with advanced cancer have been reported. [1][2][3][4][5][6][7][8][9][10][11] Knowledge of the prevalence of symptoms in patients with incurable cancer in the terminal stage is important for clinicians to provide appropriate care of cancer patients. 2 Morita et al 12 reported that clinicians can predict the probability of future symptoms from patients' characteristics, general condition and tumor location.…”
Section: Introductionmentioning
confidence: 99%